2014
DOI: 10.1093/jxb/eru062
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative phenotyping of leaf margins in three dimensions, demonstrated on KNOTTED and TCP trangenics in Arabidopsis

Abstract: SummaryThree-dimensional geometry of leaf margins is an important shape characteristic to distinguish different leaf phenotypes. Novel geometrical methods were defined, measured, and used to quantify waviness and lobiness of leaves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…• Armon et al (2014) quantified the waviness and lobiness of leaves and suggested that leaf waviness is associated with normal curvature along the margins, whereas lobiness is associated with geodesic curvature.…”
Section: The Mechanics Of Leaf Initiationmentioning
confidence: 99%
“…• Armon et al (2014) quantified the waviness and lobiness of leaves and suggested that leaf waviness is associated with normal curvature along the margins, whereas lobiness is associated with geodesic curvature.…”
Section: The Mechanics Of Leaf Initiationmentioning
confidence: 99%
“…It turns out that it is a non-trivial task to be flat. It was shown that a negative feedback regulatory circuit is required to avoid a bumpy leaf structure, which is distinctively different from the smooth, flat leaves we are used to and take for granted (Armon et al 2014).…”
Section: Necessity For Regulationmentioning
confidence: 99%
“…[1][2][3][4][5] Experimental and theoretical research has been motivated by the availability of new stimuli-responsive materials and their patterning methods, 6-10 the desire to understand and mimic the mechanics of biological systems, 4,[11][12][13][14][15] and by advances in the development of theoretical models. [1][2][3][4][5] Experimental and theoretical research has been motivated by the availability of new stimuli-responsive materials and their patterning methods, 6-10 the desire to understand and mimic the mechanics of biological systems, 4,[11][12][13][14][15] and by advances in the development of theoretical models.…”
Section: Introductionmentioning
confidence: 99%